Acute-on-chronic liver failure in an adult secondary to autoimmune hepatitis: a case report - Molina Calderón, Alonso José; Tamay, David Godínez; Hernández, Yari Esilde Baeza (International Journal of Research in Medical Sciences, 2024)
Autoimmune hepatitis (AIH) is a rare inflammatory liver disease mediated by the immune system and characterized by circulating autoantibodies. It can progress to cirrhosis and acute-on-chronic liver failure if the diagnosis is overlooked and treatment is delayed. A 35-year-old male was hospitalized for fever and jaundice. A liver ultrasound documented chronic liver disease with signs of portal hypertension and ascites. An evaluation for the etiology of chronic liver disease ruled out Hepatitis B and C, HIV, Type 2 diabetes mellitus, non-alcoholic fatty liver, alcohol, hepatotoxic drug use were denied, leading to the request for antinuclear antibodies (ANA) and anti-smooth muscle antibodies (SMA), which were positive, guiding us towards the diagnosis of autoimmune hepatitis, experiencing acute decompensation of chronic liver disease associated with the rapid onset of multiorgan failure secondary to urinary tract infection. AIH can progress to cirrhosis and terminal liver failure. In this case, our patient was asymptomatic before hospital admission, presenting with jaundice and fever, diagnosing chronic liver disease secondary to autoimmune hepatitis presenting acute-on-chronic liver failure secondary to complicated urinary tract infection. The treatment for AIH is oral corticosteroids. Broad-spectrum antibiotics were initiated without success, resulting in a fatal outcome. AIH is a disease that needs to be diagnosed by ruling out the main causes of chronic liver disease as it can initially present asymptomatically and, if untreated, can evolve into acute liver failure, chronic liver disease, and acute-on-chronic liver failure, which can be avoided with timely corticosteroid treatment.